An Evaluation of the Management Training Programme - Arbatauskas, Artūras (Acta Paedagogica Vilnensia, 1997)
One of the problems of management training is the „transfer problem" Positive transfer means the degree to which trainees effectively apply the knowledge, skills, and attitudes gained in a training context to the job. Head teachers and educational administrators become more and more sceptical about the usefulness of management training if it doesn’t guarantee positive changes in schools, afterwards. The purpose of this paper is to try to find what kind of management training and how can improve transfer in a particular case. The evaluation method used would respond to the usual problems with evaluations of in-service courses: a lack of systematic evaluation tradition, training influences its ultimate goals through a chain of events, the effect of training is a long-term, nonlinear process. The evaluation will test these hypotheses: an agreement with trainees after a course about intended changes in their schools and a follow-up of the implementation of those changes can improve the transfer; the results of a transfer can cause changes in trainees’ expectations about management training.